The stalled transformation of food processing in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
We assess the status and effects of the twin crises (COVID-19 and the military coup) on different segments (production, trade, and consumption) of Myanmar’s food processing sector. Since 2020, we note overall a stalled transformation in food processing in the country: 1. Production (post-farm): The food-processing sector – and especially rice milling – is shown to be very important, making up more than 80 percent of the revenue and value addition of the local industrial sector. The sector suffered substantially from the twin crises, as seen by reduced output and limited new investments in the two most recent years. 2. International trade: Myanmar is in most years a net agricultural exporter (in value terms). However, food exports are dominated by unprocessed and minimally processed products while food imports are mostly more expensive processed foods. While there was fast growth in international food trade between 2009 and 2019, new central bank regulations – focused on an import-substitution strategy to mitigate foreign exchange constraints – have altered trade substantially since. 3. Consumption: The categories of unprocessed and especially of minimally processed food products represent 64 and 23 percent of calories and food expenditures respectively, reflecting the importance of rice in Myanmar’s food economy. After the twin crises, the value of food consumption significantly decreased by 30 and 36 percent for rural and urban areas respectively between 2020 and 2022. However, consumption levels for rural residents are still lower after the crises than those of urban ones. Moreover, while real food consumption expenditures declined significantly for all income groups, the poorest suffered most from the crises as seen in the higher reduction of expenditures for the poorest quintiles (by 31 and 39 percent in rural and urban areas respectively).